Analysis of Molecular Docking Chemical Content of Lime (Citrus aurantiifolia (Christm.) Swingle) Against Diabetes Mellitus Therapy Targets and Prediction of Pharmacokinetic Profiles and Toxicity - Ismah, Kadar; Supriyadi (Open Access Indonesian Journal of Medical Reviews, 2022)
Diabetes mellitus drugs currently available are sulfonylureas, biguanides, thiazolidines, and alpha glucoside inhibitors which are widely used to control hyperglycemia. These drugs cannot prevent complications of diabetes, and these drugs should not be used continuously because it causes undesirable pathological conditions. The essential oil in lime peel is rich in phenolics, especially flavonoids, which can prevent oxidative stress. This research was carried out computationally to determine the affinity of the compound mechanism in lime, pharmacokinetic profile, and toxicity of the chemical content of lime which is thought to have antihyperglycemic activity using chemoinformatics studies. The hardware used is an Asus laptop X441UB-GA502T Intel Core I5 – 8250 DDR 4 4GB HD 1TB VGA mix 110 2GB screen 14 "DVD-RW WIN 10 ORI. The software used is PLANTS (PROTEIN-LIGAND ANT SYSTEM), YASARA, Marvin sketch, Swisstargetprediction, SwissADME, and Toxtree. All compounds in lime were most active against the target protein PPARγ with an average value of -78.0092, while the positive control value of thiazolidinediones was -90.3393. The highest inhibitory affinity of the compound contained in lime was hesperidin with the target protein DPP-4 of -113.614, higher than the positive control sitagliptin with an inhibitory affinity value of -107.591. Hesperidin absorption in the digestive tract is low, the topology polar surface area (TPSA) value is 234.29Å2, and low polarity and high lipophilicity. There are unexpected heterocyclic compounds, so it becomes a warning against the potential for genotoxic carcinogenicity, namely oxygen element "o".